Odpowiedzi

2010-03-09T20:53:59+01:00
(1) a+b+c=36
(2) a+b=2c
(3) b+c=a+10

podstawiamy (2) do 1()
3c=36, stąd c=12
dostajemy teraz
a+b=24
b+12=a+10, czyli
(4) a+b=24
(5) b=a-2
znów podstawiamy (5) do (4)
2a=26, stąd a=13, czyli b=11

Te liczby to 13, 11 i 12
Najlepsza Odpowiedź!
2010-03-09T21:02:46+01:00
A=I liczba
b=2 liczba
c=3 liczba

a+b=2c
b=2c-a

b+c=a+10
b=a+10-c

b=b
a+10-c=2c-a

{2a-3c=10
{a+b=2c/x-2

{2a-3c=10
{-2a-2b=-4c
_________
-2b-3c=10-4c
-2b+c=10

b+c=a+10
b+c-a=10
b+c-a=-2b+c


3b=a
-2b+c=10
2a-3c=10
2x3b-3c=10
6b-3c=10

a=13
b=11
c=12